Corrosion Resistance Enhancement of the Materials Surface (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains different corrosion resistance topics like: corrosion behavior of coated low-carbon steel in a simulated PEMFC environment; some brassicaceae extracts as potential antioxidants and green corrosion inhibitors; electrochemical impedance analysis for corrosion rate monitoring of Sol–Gel protective coatings in contact with nitrate molten salts for CSP applications; comparing the corrosion resistance of 5083 Al and Al2O33D/5083 Al composite in a chloride environment; microstructural, corrosion resistance, and tribological properties of Al2O3 coatings prepared by atmospheric plasma spraying; the influence of friction stir surface processing on the corrosion resistance of Al 6061; the preparation of one-dimensional polyaniline nanotubes as anticorrosion coatings; in vitro analysis of FeMn-Si smart biodegradable alloy; corrosion resistance of electrochemically synthesized modified zaccagnaite LDH-type films on steel substrates; new Zn3Mg-xY alloys; characteristics, microstructural evolution, and corrosion and immersion behaviors of carbon steel; phosphate carbon steel and phosphate and painted carbon steel in saltwater.